Business Finance - Peirson, Graham [et. al] (North Ryde McGraw-Hill, 2007)
"Business Finance has been written by a highly regarded author team and is a proven authoritative text, having been the Australian market leader for over 30 years. This new ninth edition has been extensively updated and revised to ensure that it is engaging and accessible, and continues to meet the needs of students. It is a textbook for today and a reference tool for tomorrow's finance practitioner."--McGrawHill.
Includes Index, Glossary and Colred Illustrations.
Keywords: Business enterprises -- Finance